Influence of UTCP on the employment of female workers and the supply of labor force. - Mingming Li (Public Library of Science (PLoS), 2021)
In recent years, China has introduced the Universal Two-Child Policy (UTCP), which means that a couple can have two children. The implementation of this policy may affect female employment. Based on this background, this work aims to the impact of UTCP on the number and employment of Chinese women workers, and find out the countermeasures for the adverse impact of the policy. Firstly, the role of the Propensity Score Matching-Differences in Differences model is introduced, and the average and dynamic effects of UTCP on women's employment are discussed by using the Propensity Score Matching model. Secondly, the survey data on issues related to female employment after the implementation of UTCP from 2016 to 2020 is analyzed. Finally, a conclusion is drawn according to the survey data. The results demonstrate that the implementation of UTCP widens the income gap between men and women. Meanwhile, the younger the couple, the greater the income gap. Besides, the unemployment rate changes slightly after the introduction of the policy. As the growth rate of female income is significantly lower than that of men of the same age, UTCP has little impact on the employment of Chinese female workers, but has a great impact on the quality of employment. Among all the respondents, the proportion of employed men is higher than employed women, which is about 64% ~ 65%. However, it is still unknown whether age, education, family characteristics, nationality, occupations, and economic development of the province have a certain impact on female income, which is worth noting by follow-up research. On the whole, the full liberalization of the second child has little impact on the employment of female workers in China, but has a great impact on the quality of employment. The present work lays a foundation for the study of the impact of UTCT on female employment in future, and offers a certain reference for the further study of the impact of the policy on employment in the future.